The Integration of Javanese Culture in The Delivery of Religious Messages - Yunus, Muhammad; Habibi, Erfan; Ubaidillah, Ubaidillah; Alfatani, Ifan Ali (Proceedings of Annual Conference for Muslim Scholars, 2024)
This research explore in the integration of Javanese culture in the delivery of religious teachings at Pondok Pesantren Mambaul Falah Bondowoso. The focus is on how the pesantren merges the local cultural elements, including language, the arts, and traditions to further identify and deepen Islamic preaching. This study attempts to explain the implications of integrating such culture for santri's religious identity and social harmony. This qualitative research was performed with phenomenological approach. data have been collected through interviews, participant observation, and document analysis. the result of this research is inculcating Javanese Culture-scoped, such as language and music (hadrah with gamelan)-builds tolerance and inclusive attitude. The thought can also increase social cohesion within the community of Bondowoso. The paper concludes that, though cultural integration can deepen the understanding of religion, it also cements harmony and respect for diversity within the community.